Effects of vitamins and mineral proteinates on growth performance and pork quality in finishing pigs - J S Park; Donald H Kropf; K A Hachmeister; Robert H Hines; C L Jones; D W Dean; D J Lee; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 2000)
From 185 to 225 lb BW, no differences in ADG, ADFI, or F/G occurred among pigs fed diets without or with vitamin and trace mineral premixes. Then, from 225 to 266 lb BW, a special premix with megadoses of vitamin E, vitamin C, Mg-proteinate, and Feproteinate was added to the diets of half the pigs given the previous treatments. Growth performance was not different among pigs fed diets without vitamin or with the KSU and special vitamin and mineral premixes. Also, meat quality (color, marbling, and firmness scores; drip, thawing, and cooking losses; shear force; and Hunter L*a*b*) was not affected by inclusion of the KSU and special vitamin and mineral premixes.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Vitamins; Minerals; Pork quality